9x+5=7-(6x-9)

Simple and best practice solution for 9x+5=7-(6x-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+5=7-(6x-9) equation:


Simplifying
9x + 5 = 7 + -1(6x + -9)

Reorder the terms:
5 + 9x = 7 + -1(6x + -9)

Reorder the terms:
5 + 9x = 7 + -1(-9 + 6x)
5 + 9x = 7 + (-9 * -1 + 6x * -1)
5 + 9x = 7 + (9 + -6x)

Combine like terms: 7 + 9 = 16
5 + 9x = 16 + -6x

Solving
5 + 9x = 16 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
5 + 9x + 6x = 16 + -6x + 6x

Combine like terms: 9x + 6x = 15x
5 + 15x = 16 + -6x + 6x

Combine like terms: -6x + 6x = 0
5 + 15x = 16 + 0
5 + 15x = 16

Add '-5' to each side of the equation.
5 + -5 + 15x = 16 + -5

Combine like terms: 5 + -5 = 0
0 + 15x = 16 + -5
15x = 16 + -5

Combine like terms: 16 + -5 = 11
15x = 11

Divide each side by '15'.
x = 0.7333333333

Simplifying
x = 0.7333333333

See similar equations:

| 15x^2+13x-6= | | X+4X+9+6X-3=180 | | t*6=11 | | .5x=y+100 | | V^2+8=-v+8 | | b-17=12 | | 15x^2+92x=60 | | 5x=y-100 | | 10+3x=-44 | | 8a^2+8a-99=-3 | | x=5y+90 | | h+10=17 | | -5+5=13x-2-12x | | 5(2x+3)=33 | | y=3lnx-7 | | -3x+80+13x-105+5x+40=180 | | 2z^2+15z-3=13z | | h-9=2 | | -2x+8=4+-2x+8 | | 4+p=52 | | -[3z^2+6z-(2z^2-3z)]+[(8z^2-[5z-z^2])+5z^2]= | | 2x^2-92x=0 | | 4x+2x=58 | | 6r^2+17r+10=0 | | 19-3a=-2n | | (6u^2-14u)/(2u^2-8u) | | x-y=11/2x-y=19 | | 170=5v+3(6-8v) | | h+44=50 | | (1/x)=1 | | 4(1+6v)=-140 | | 3-4x(2+3x)=1(1+5x) |

Equations solver categories